2010
DOI: 10.1111/j.1083-6101.2010.01520.x
|View full text |Cite
|
Sign up to set email alerts
|

Texting as a life phase medium

Abstract: SMS has grown to be a common form of interaction in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 12 publications
3
81
0
Order By: Relevance
“…The analysis of teens' use of mobile communication has described its contribution to a sense of teen culture (Goggin and Crawford, 2011;Ito et al, 2005). Following a slightly different direction, there has also been analysis of how mobile communication ebbs and flows as teens move through the different phases of adolescence (Helles, 2009;Ling, 2010). There has also been analysis of how the mobile phone plays into the sense of teen self-image (Skog, 2002) and how texting becomes a way for teens to exploit the plasticity of the language Baron and Ling, 2011;.…”
Section: Teen Use Of Mobile Communicationmentioning
confidence: 99%
“…The analysis of teens' use of mobile communication has described its contribution to a sense of teen culture (Goggin and Crawford, 2011;Ito et al, 2005). Following a slightly different direction, there has also been analysis of how mobile communication ebbs and flows as teens move through the different phases of adolescence (Helles, 2009;Ling, 2010). There has also been analysis of how the mobile phone plays into the sense of teen self-image (Skog, 2002) and how texting becomes a way for teens to exploit the plasticity of the language Baron and Ling, 2011;.…”
Section: Teen Use Of Mobile Communicationmentioning
confidence: 99%
“…Thus, the study makes a theoretical contribution by comparing the extent to which each of these alternative perspectives holds up in the findings. because the technology itself is a salient part of young adults' social life (Ling, 2004(Ling, , 2010. Indeed, in their study of Internet users, Shah, Kwak, and Holbert (2001) and Kwak, Poor, and Skoric (2006) found the computer-based Internet to be a more useful resource for civic and political engagement among younger users than older adults.…”
Section: The Mobile Reinforcement Hypothesis Vs the Mobile Facilitatmentioning
confidence: 99%
“…More generally, social phenomena with differential adoption rates can sometimes be characterized as either based upon cohorts or on life phases (Ling, 2010). Whereas cohortbased phenomena stay with a particular group society as they age, such as a 1970s'music preference staying with those who were teenagers in the 1970s, life-phase phenomena, such as liking current chart music, are prevalent within a particular age group.…”
Section: Sns Adoptionmentioning
confidence: 99%
“…Whereas cohortbased phenomena stay with a particular group society as they age, such as a 1970s'music preference staying with those who were teenagers in the 1970s, life-phase phenomena, such as liking current chart music, are prevalent within a particular age group. Research with multiple groups of Norwegians has shown that the use of text messaging is a life-phase activity that is prevalent among older teens and those in their early 20s (Ling, 2010), perhaps because of a range of specific youth-oriented social uses (Oksman & Turtiainen, 2004). As another type of information and communication technology, this suggests that SNS use also might be a life-phase activity.…”
Section: Sns Adoptionmentioning
confidence: 99%